1982
DOI: 10.1021/ja00389a053
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a tetrahedral intermediate and its anion in a hydrolysis reaction. Ring opening of a quinazolinium ion

Abstract: The behavior of the 3,4-dihydro-1,3-dimethyl-4-0xoquinazolinium ion (Q') in basic aqueous solution (pH 7-1 4 ) has been studied. Kinetic studies afforded information about four distinct processes: (a) the relatively fast equilibration of Q' with its pseudobase QOH; (b) the slower equilibration of the manifold comprised of Q' , QOH, the pseudobase anion QO-, and the ring-opened form, a formanilide derivative, F (equilibrium is approachable starting from Q' or from F, which exists in solution as a 3:1 mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…44 In the earlier work (Tables I, III, and IV)la the stored curve was plotted out onto large graph paper, digitized, and then analyzed.44 For the later studies,18 the waveform recorder was interfaced to an Apple II microcomputer. 59 In cases where the decay of transient cyclohexadienones5 interfered with the infinity readings, the monitoring wavelength was set at 275 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In the earlier work (Tables I, III, and IV)la the stored curve was plotted out onto large graph paper, digitized, and then analyzed.44 For the later studies,18 the waveform recorder was interfaced to an Apple II microcomputer. 59 In cases where the decay of transient cyclohexadienones5 interfered with the infinity readings, the monitoring wavelength was set at 275 nm.…”
Section: Discussionmentioning
confidence: 99%
“…gave 72 mg of a red solid with mp and NMR properties identical with those of quinone 13. The 13C NMR spectrum indicated that ,80 had been incorporated on C-4 and the CIMS data indicated that the product consisted of 68% of 180-labeled quinone 14 and 32% of unlabeled quinone 13: 13C NMR (Me2SO-46) & 14.60 (CH3), 25.73 (Ctf2CH2N), 38.56 (CH2N), 59.37 (OCH2), 106.31 (C-6), 119.43 (C-3), 122.65 (C-2), 123.15 (C-3a), 132.05 (C-7a), 156.11 (C02), 159.47 (C-5), 178.50 (C-7), 178.70 (C-4 of 14, rel intensity 41.6), 178.75 (C-4 of 13, rel intensity 28.8); CIMS mje (rel intensity) 279 (51.9 MH+), 281 (100.0), 282 (17.2).…”
mentioning
confidence: 99%
“…The reactions are, however, not unexpectedly, rather indiscriminate and complex reaction mixtures were obtained. Only rutaecarpine and dehydrorutaecarpine (30) were identified among the array of products. In this connection it was found that 2,3-dichloro-4,5-dicyanoquinone (DDQ) in dioxane readily converted 1 into 30.27 Finally it might be added that the interaction of 19 with Hg(OAc)2 was studied already by Clauder,28 who, however, had erroneously assigned to 19 structure 21.…”
mentioning
confidence: 99%
“…Subsequently work was done to demonstrate a tetrahedral intermediate in this hydrolysis reaction 38. Kinetics for each equilibrium in this reaction were analysed using UV and NMR spectroscopy and the mechanism they propose matches that proposed here.…”
mentioning
confidence: 77%
“…The change in ratio in different solvents was puzzling, however, until now: interchange between rotamers is possible, but only through the tetrahedral intermediate 36, which can open to yield either rotamer. 38 Although bond breaking is required to interchange these, and hence they could be…”
Section: Rotamers and Cyclic Speciesmentioning
confidence: 99%